Analysis of Labor Market Transformation in the Context of Industry 4.0 - Stryzhak Olena (Studia Universitatis Vasile Goldis Arad, Seria Stiinte Economice, 2023)
The digitalization of the economy and society in the context of Industry 4.0 affects the labor market. New jobs are being created with new personnel requirements. At the same time, digitalization processes affect countries and sectors of the economy in different ways. The number of employed is declining in some sectors and increasing in others. The ratio of people employed in different industries also differs from country to country. As the digitalization of production relations intensifies, transformation processes in the labor market will increase. In the context of the actualization of digital changes in modern society, the aim of the article is to analyze the labor market under the digitalization of economic relations. The World Development Indicators (WDI) and Digital Intelligence Index (DII) were used to realize the purpose of the study. The study covers 89 countries for 2019. Correlation analysis, standardization, cluster analysis and analysis of variance were used as methods in the research. As a result of the study, the following conclusions were obtained. A strong relationship was found between Gross Domestic Product (GDP) and DII for the whole sample. The cluster analysis process found that the variables form three clusters with values of most indicators by group: at the high, the average and the low levels. Plots of mean and confidence intervals for the variables in each cluster were also plotted. Correlation coefficients were calculated for each cluster. It was found that each group has its own internal patterns.